Protective and Therapeutic Effects of Orlistat in Combination with Elettaria cardamomum “Cardamom” Extract on Learning, Memory, Anxiety, and Neuroinflammation in Obese Mice - Anfal AL-Dalaeen; Nour Batarseh; Nadine N. Abdelhadi; Sally Atawneh; Reem AbuKashef; Ali Mosa Ra-shid Al-Yasari (Medicina)
Introduction and Objective: Obesity has increased worldwide, and existing anti-obesity medications have treatment limitations that diminish their overall benefits. This study aimed to investigate the effects of orlistat in combination with Elettaria cardamomum “Cardamom” (CAR) extract on working memory, recognition memory, anxiety, and inflammation within hippocampal tissue. Methods: Mice were categorized into two groups: a control group (CD) and a cafeteria diet (CAF) group induced with obesity (CAF) for 10 weeks. The groups were then subdivided into a CAF group treated with orlistat (CAF-ORL), a CAF group treated with orlistat and Elettaria cardamomum (CAF-ORL-CARD), and a group that continued on the CAF. The CAF-ORL group received orlistat at a dosage of 10 mg/kg/day for four weeks, while the CAF-ORL-CARD group received 10 mg/kg/day of orlistat and 500 mg/kg of CAR extract via oral gavage. In the 14th week, various assessments were conducted, including the novel object recognition (NOR) test, Y maze test, marble-burying test (MBT), open-field test, and TNF-α levels in the hippocampus. Result: TNF-α levels in the hippocampal tissue of the CAF group were elevated compared to the CD group (p < 0.01), whereas the CAF-ORL group exhibited reduced TNF-α levels compared to the CAF group (p < 0.01). Moreover, TNF-α levels in the CAF-ORL-CARD group were significantly lower than in the CAF-ORL group (p < 0.01). The recognition index was notably higher in the CAF-ORL group compared to the CAF group (p < 0.01) and higher in the CAF-ORL-CARD group compared to the CAF-ORL group (p < 0.01). However, there were no changes in the open-field test and Y maze test (p > 0.05). Conclusions: Orlistat combined with CAR has positive effects on neuroinflammation and memory, suggesting that this combination may offer potential therapeutic benefits for cognitive impairments and hippocampal dysfunction associated with obesity.